Investigação da fauna flebotomínica e sua infecção por Leishmania spp., no município de Lavras, MG, Brasil - Castro, Joseane Camilla de (2017)
Leishmaniasis is a neglected disease that affects a large part of the world population and it’s caused by protozoa of the genus Leishmania. Leishmaniasis may manifest in its integument form, causing dermatological lesions with different clinical characteristics or in its viscerotropic, potentially fatal form. The different species of Leishmania are transmitted by hematophagous dipterans of the family Psychodidae, also known as phlebotomines. Knowing the phlebotominal fauna of a region is of fundamental importance to guide the actions in health surveillance related to the prevention and control of leishmaniasis. Considering cases of human tegumentary leishmaniasis and human and canine visceral leishmaniasis have been reported for the municipality of Lavras, this study aimed to verify the presence of sandflies and their natural infection by different species of the genus Leishmania. Then, collections were systematized using HP-type, light traps were carried out between February 2016 and March 2017. Traps were installed in eight residences that had dogs confirmed serology for Leishmania infantum infection in areas of preserved vegetation or Semi preserved. A total of 86 specimens of sand flies were collected, 60 females and 26 males. The identification was performed using the classification proposed by Galati (2003), and the following species were identified: Lutzomyia longipalpis, Migonemyia migonei, Evandromyia cortelezzi, Ev. lenti, Ev. sallesi, Nyssomyia whitmani, Brumptomyia sp., Psathyromyia lutziana, and Pressatia sp. Five females of the Lu longipalpisspecies were infected by Leishmania braziliensis. Despite the small number of specimens collected, there was a great diversity of species in the study area. In addition, the encounter of specimens of Lu. longipalpis naturally infected with Leishmania braziliensis, shows the need to evaluate vector competence since there is no literature report of this natural interaction between these species.